The complete chloroplast genome sequence of Populus deltoides 'Siyang-2'. Issue 1 (2nd January 2020) - Su, Tao; Han, Mei; Min, Jie; Cao, Dan; Pan, Huixin; Liu, Yuxin
Abstract: Populus deltoides 'Siyang-2' is an improved variety of forest trees that have been identified recently. It shows superior growth performance compared to other local cultivars in the region of Yangtze-Huaihe in China. In this study, the whole chloroplast (cp) genome sequence of 'Siyang-2' was assembled and characterized by high-throughput sequencing data. The complete cp genome was 156, 957 bp in length, containing a large single-copy region (LSC) of 85, 096 bp, and a small single-copy region (SSC) of 16, 563 bp, which were separated by a pair of 27, 649 bp inverted repeat regions (IRs). The cp genome contained 131 genes, including 86 protein-coding genes, 37 tRNA genes, and 8 ribosomal RNA genes. Most of the gene species occur as a single copy, while 20 gene species occur in double copies. The overall GC content of 'Siyang-2' cp genome is 34.6%, while the corresponding values of the LSC, SSC, and IR regions are 34.5%, 30.6%, 41.9%, respectively. The complete cp genome provides valuable phylogenetic and cp genetic engineering studies of this important improved poplar species P. deltoides 'Siyang-2'.